IDENTIFIKASI SIBUTRAMIN HCL PADA JAMU PELANGSING YANG DIJUAL DI PASAR BESAR KOTA MALANG MENGGUNAKAN METODE KLT - CARMIA DEWI SALMAA; Muhammad Hasan Wattiheluw (Politeknik Kesehatan Kemenkes Malang, 2022)
Sibutramine Hydrochloride is a weight loss drug, a group of strong drugs that can only be obtained and can only be used based on a doctor's prescription because it can increase blood pressure. Sibutramine HCl is absolutely not allowed to be found in slimming herbs in accordance with the regulation of the Indonesian POM No. KH.00.01.43.2773.2008 concerning traditional medicine containing BKO. The identification chosen in this study used the Thin Layer Chromatography (TLC) method, to determine the presence or absence of the addition of medicinal chemicals (BKO) in slimming herbs. Sibutramine HCl analysis was carried out qualitatively using the mobile phase of TLC, namely (acetone: chloroform). From the results of the study, obtained 3 out of 4 samples of slimming herbs containing the drug chemical sibutramine hcl with an Rf value of 0.77 There are 75 percent slimming herbs sold in Pasar Besar, Malang City which contain BKO Sibutramine HCl. Therefore, it is necessary to monitor and inspect traditional medicine traders by the Malang City Health Service and BPOM on a regular basis to avoid the use of BKO in slimming herbs sold in the Pasar Besar area, Malang City.